2020
DOI: 10.1002/advs.202002328
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Regulation of Macrophage Polarization to Enhance Osseointegration Under Diabetic Conditions Using Injectable Silk/Sitagliptin Gel Scaffolds

Abstract: As a chronic inflammatory disease, diabetes mellitus creates a proinflammatory microenvironment around implants, resulting in a high rate of implant loosening or failure in osteological therapies. In this study, macroporous silk gel scaffolds are injected at the bone–implant interface for in situ release of sitagliptin that can regulate macrophage response to create a prohealing microenvironment in diabetes mellitus disease. Notably, it is discovered that sitagliptin induces macrophage polarization to the M2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Mechanistically, M2 macrophages secrete osteogenic factors that stimulate the differentiation and activation of MSCs and subsequently increase bone mineralization. Recent data have demonstrated that the polarization of M2 macrophages is capable of stimulating MSCs into mature osteoblasts and increasing bone mineralization in vitro . , Consistently, our study indicated that interventions that favor M2 macrophage polarization might be a novel approach for bone fracture treatment.…”
Section: Resultssupporting
confidence: 86%
“…Mechanistically, M2 macrophages secrete osteogenic factors that stimulate the differentiation and activation of MSCs and subsequently increase bone mineralization. Recent data have demonstrated that the polarization of M2 macrophages is capable of stimulating MSCs into mature osteoblasts and increasing bone mineralization in vitro . , Consistently, our study indicated that interventions that favor M2 macrophage polarization might be a novel approach for bone fracture treatment.…”
Section: Resultssupporting
confidence: 86%
“…Mechanistically, M2 macrophages secrete osteogenic factors that stimulate the differentiation and activation of MSCs, and subsequently increase bone mineralization. Recent data have demonstrated that M2 macrophages polarization are capable to stimulate MSCs into mature osteoblasts and increase bone mineralization in vitro [34,35]. Consistently, our study indicated that interventions that favor M2 macrophage polarization may be a novel approach for bone fracture treatment.…”
Section: M2 Macrophage Polarization Induces Mscs Towards Osteoblasitc Differentiation In Vitrosupporting
confidence: 86%
“…The typical immunomodulatory mechanism of biomaterials for tissue repair is to switch the macrophage phenotypes from pro-inflammatory M1 to anti-inflammatory M2 21 , 54 , 55 . For bone implants, studies have showed that excessive M1 macrophages can cause bones absorption, which is an important factor leading to implant loosening or implantation failure 56 , 57 .…”
Section: Resultsmentioning
confidence: 99%